1980
DOI: 10.1002/dev.420130503
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of behavioral sensitivity to glycine in the chick embryo

Abstract: Strychnine (STR), glycine (GLY), and gamma-aminobutyric acid (GABA) were injected intravenously into 6- and 7-day chick embryos and subsequent effects upon spontaneous motility were observed. In 7-day embryos STR alone increased motility and when injected simultaneously with GLY antagonized the GLY-induced motility decrements; STR did not antagonize GABA-induced motility decrements. In 6-day embryos STR injected alone had no effect on motility, but did antagonize motility decrements induced by the simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Specific receptor agonist and antagonist treatments could be used to potentiate or block the effects of strychnine on locomotor behavior. In prior research embryonic exposure to strychnine in the chick has been found to also increase locomotor activity (Oppenheim and Reitzel 1975; Reitzel and Oppenheim 1980; Sedlacek 1992). This suggests a more general action of glycinergic receptors in the development of locomotor function across vertebrate species.…”
Section: Discussionmentioning
confidence: 93%
“…Specific receptor agonist and antagonist treatments could be used to potentiate or block the effects of strychnine on locomotor behavior. In prior research embryonic exposure to strychnine in the chick has been found to also increase locomotor activity (Oppenheim and Reitzel 1975; Reitzel and Oppenheim 1980; Sedlacek 1992). This suggests a more general action of glycinergic receptors in the development of locomotor function across vertebrate species.…”
Section: Discussionmentioning
confidence: 93%
“…Descending neural inputs are generally believed to have a net excitatory drive and descending inhibitory inputs are reported to be active only after E 15 (for review, see Corner, 1990). However, embryonic motility decreases following administration of y-aminobutyric acid (GABA), an effect that can be reversed by bicuculline or picrotoxin (Reitzel, Maderdrut, and Oppenheim, 1979), and motility increases followingadministration of strychnine, a glycine antagonist (Reitzel and Oppenheim, 1980) as early as E7, suggesting that inhibitory mechanisms are already functional at the spinal cord by ElO. Findings from spinally mediated locomotion in the lamprey suggests that both excitatory ( i.e., N-methyl-D-aspartic acid, kainate) and inhibitory (i.e., glycine, GABA) synaptic actions may account for temporal variations observed in rhythmical motor output patterns (Grillner,Walltn,and Brodin,199 1 ).…”
Section: 5 Gl Cycle Periodmentioning
confidence: 99%
“…Because of its amenability to embryonic microsurgery and electrophysiological and neuropharmacological experiments, the chick embryo is a particularly useful subject for studies concerning embryogenesis. Many of the aforementioned experiments attesting to the fundamental role of GABA in early neurogenesis, especially those that focused on embryonic motility, have also been performed on chick embryos (Renaud et al, 1978;Pittman and Oppenheim, 1979;Reitzel et al, 1979;Toutant et al, 1979;Reitzel and Oppenheim, 1980;McLennan, 1983;Maderdrut et al, 1986;O'Donovan and Landmesser, 1987;O'Donovan, 1987O'Donovan, , 1989O'Donovan et al, 1992;Ho and O'Donovan, 1993). Despite many physiological, pharmacological, and behavioral experiments concerning GABA-mediated events in neural development, the neurochemical localization of GABA in the central nervous system of chick embryos has received little attention.…”
mentioning
confidence: 99%